An ancestral NB-LRR with duplicated 3′UTRs confers stripe rust resistance in wheat and barley - Chaozhong Zhang; Lin Huang; Huifei Zhang; Qunqun Hao; Bo Lyu; Meinan Wang; Lynn Epstein; Miao Liu; Chunlan Kou; Juan Qi; Fengjuan Chen; Mengkai Li; et al. (Nature Communications, 2019)
Stripe rust is a serious threat to wheat production. Here, the authors reveal that the resistance gene, only present in the wheat progenitor Aegilops tauschii and its derived synthetic wheat, encodes a nucleotide oligomerization domain-like receptor and confers resistance in common wheat and barley.